2018
DOI: 10.3892/or.2018.6763
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑466 inhibits the aggressive behaviors of hepatocellular carcinoma by directly targeting metadherin

Abstract: Numerous microRNAs (miRNAs) have been demonstrated to be downregulated or upregulated in hepatocellular carcinoma (HCC) and play important roles in its occurrence and development. Therefore, the investigation of miRNAs and their functions implicated in the genesis and development of HCC may provide key clues for the identification of effective therapeutic approaches for patients with this disease. The aims of the present study were to detect miRNA-466 (miR-466) expression in HCC tissues and cell lines and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 177 miRNA-466 stimulates apoptosis and decreases growth capacity of HCC cells via down-regulating metadherin expression. 178 miRNA-466 can also affect Wnt/β-catenin signaling in HCC. Increasing miRNA-466 expression triggers apoptosis and diminishes growth and migration of HCC cells.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“… 177 miRNA-466 stimulates apoptosis and decreases growth capacity of HCC cells via down-regulating metadherin expression. 178 miRNA-466 can also affect Wnt/β-catenin signaling in HCC. Increasing miRNA-466 expression triggers apoptosis and diminishes growth and migration of HCC cells.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…Increased expression of has-miR-466 inhibited the in vitro proliferation and invasion of osteosarcoma cells [55]. Similarly, a decrease in hsa-miR-466 expression has been demonstrated in hepatocellular carcinoma cells, and an increase in hsa-miR-466 expression inhibits proliferation, induces apoptosis and reduces the metastatic potential of the tumour by targeting MTDH [56]. In prostate cancer, a decrease in hsa-miR-466 expression was demonstrated due to the activity of the long noncoding RNA TUC338.…”
Section: Discussionmentioning
confidence: 87%
“…miRNAs are highly conserved RNAs that exhibit a high degree of homology between different species. Jia et al ( 37 ) demonstrated that miR-466 inhibits the aggressive behavior of hepatocellular carcinoma by directly targeting metadherin. However, the results of the present study demonstrated that knockdown of miR-466g reversed the activation of HSCs and the downregulation of α-SMA and Col-1 expression induced by lnc-MBI-52 knockdown.…”
Section: Discussionmentioning
confidence: 99%